Iridocorneal endothelial syndrome - Ma, Hua; Xia, Mingfang; Gu, Qing; Zheng, Lingling; Ha, Shaoping (Frontiers in Ophthalmology, 2025)
The iridocorneal endothelial syndrome encompasses a spectrum of ocular disorders predominantly affecting one eye in young to middle-aged women, typically without a familial predisposition. The hallmark feature of iridocorneal endothelial syndrome is the migration of corneal endothelial cells towards the iridocorneal angle and onto the iris. This syndrome comprises three distinct clinical variations: progressive essential atrophy of the iris (including corectopia, iris atrophy, or iris hole), Chandler syndrome (characterized by corneal edema with mild to absent changes in the iris), and Cogan-Reese syndrome (manifesting as nodular pigmented lesions on the front surface of the iris). In cases involving corneal manifestations, such as corneal edema or decompensation, options like Descemet’s stripping automated endothelial keratoplasty and Descemet membrane endothelial keratoplasty may be considered for optimal management. For instance, conditions affecting the iris, such as an iris cavity, multiple pupils, or photophobia, may make femtosecond-assisted keratopigmentation a treatment option. In cases of glaucoma secondary to iridocorneal endothelial syndrome, trabeculectomy with mitomycin C and the implantation of a glaucoma drainage device have been shown to reduce intraocular pressure effectively. At the same time, retrocorneal membrane interception-enhanced peripheral iridectomy has demonstrated significant efficacy.